Correlation between Language Learning Strategies and Thinking Styles on Learning Outcomes of Senior High School Students - Nur Maulani; Sahril Nur; Nur Aeni; Nur Aeni (Journal of Excellence in English Language Education, 2022)
The objectives of this paper were to see if using Contextual Teaching and Learning (CTL) for vocabulary instruction was helpful or not. The objective of this research was to determine whether there is any correlation between language learning strategies and thinking styles on learning outcomes of senior high school students in the eleventh-grade academic year 2021-2022 at SMA Negeri 2 Majene. This study is quantitative research, using survey research. The population in this study was 185 students. The researchers use random sampling in this study. The total sample that took part in this study was 50 students. Techniques for gathering information include spreading using questionnaires. Data were analyzed by correlating analysis using SPSS 25. The results showed that the Correlation Between Language Learning Strategies and Thinking Styles on Learning Outcomes of Senior High School Students in the Eleventh Grades of the Academic year 2021-2022 at SMA 2 Majene was a positive significant correlation. The conclusion, there is a considerable correlation between language learning strategies and thinking styles, and this relationship has a favorable influence on student learning outcomes.